Biorhythms in predicting coronary heart disease prognosis - O. L. Barbarash; N. V. Fomina; E. V. Mineeva; S. S. Altarev; G. A. Chumakova; A. N. Sumin; N. I. Tarasov; D. S. Krivonosov; L. S. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To study the 3-year dynamics of the association between cardiovascular events, calendar year seasons and individual annual cycle (IAC) trimesters among patients with myocardial infarction (MI).Material and methods. The study included 324 patients with Day 5-7 Q-MI and left ventricular ejection fraction ≤35 %. During the 3-year follow-up, the following cardiovascular events were registered: death, heart failure progression, repeat MI, unstable angina episodes. Based on individual date of birth, the index number of IAC month when an outcome took place, was identified. Calendar year season was also registered for all cardiovascular events.Results. Winter and summer seasons were associated with the highest risk of cardiovascular events, hospital admissions and deaths; autumn was associated with the minimal risk. The peak of coronary events and deaths was observed in the time window close to the date of birth (IAC trimesters I and IV); the trimesters with the lowest risk were II and III.Conclusion. To increase the effectiveness of predicting cardiovascular events in MI patients, annual cycles should be taken into account.